Pembangunan Perdamaian Berkelanjutan Di Burundi Pasca Perang Sipil 1993-2006 - Isrotul Fajriyah (Jurusan Ilmu Hubungan Internasional, 2016)
Burundi is one of the poorest countries in the world that suffered from prolonged ethnic conflict. Conflict between Hutu and Tutsi has brought this country into genocide on 1972 and 1993 that led into 12 years of civil war. Peacemaking effort to end violent conflict in Burundi has gone through three main phases involving regional and international organisations. As result of this peace process, the parties have signed Arusha Peace and Reconciliation Agreement on 28 August 2000. This agreement directly addressed the issue of ethnicity in Burundi and devised a power- sharing arrangement. However, peace is a fragile thing so it’s important to build strong foundation for ensuring its sustainability. Peacebuilding efforts are necessary to bring post-conflict recovery and prevent the outbreak of civil war in the future. The role of international community is also needed to support post-conflict peace-building in Burundi.